Characterization of bacteria isolated from goat manure in Beting, Kuala Pilah / Nurainshafika Ibrahim - Ibrahim, Nurainshafika (2017)
Goat manure is the waste product eliminated from the rumen of the goat resulting from the food intake by the goat. Microorganisms in goat manure would spread in abundance, once the goat manure fall onto the ground and water. Hence, the aim of this study is to characterize the bacteria isolated from goat manure. The improper handling of goat manure in Beting, Kuala Pilah may affect human health. The sample of goat manure was collected aseptically. The goat manure was preceded with a serial dilution up to 10-6 and spread on nutrient agar. The pure culture was obtained by sub-culturing each different bacteria on nutrient agar and followed by biochemical tests. The gram staining was first done for gram identification then followed by biochemical tests. The biochemical tests were citrate utilisation, eosin methylene blue agar, triple sugar iron, hydrogen sulfide and MacConkey agar test. Potential bacteria that successfully isolated from goat manure were Escherichia coli and Pseudomonas spp.. Both bacteria have caused many diseases to human.